2012
DOI: 10.1039/c2cp42174g
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between amino acid residues and flavonoid derivatives: insights into their chemical recognition

Abstract: Currently, there is a general consensus that flavonoids exert their antioxidant activity through their ability to interact with a broad range of proteins, enzymes and transcription factors rather than acting as conventional hydrogen-donating antioxidants. For this, the effect of different chemical groups of the conjugated flavonoid metabolites is apparently playing a pivotal role. Yet, many questions concerning the relevant molecular mechanisms still remain open. It is therefore crucial to gain a deeper insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…There are numerous reports of PP interacting by hydrogen bonding with lipids such as cholesterol and phospholipid bilayers and cell membranes using multiple techniques. A study in this Journal showed that tea catechins formed multiple hydrogen bonds with a phospholipid . Additional support of hydrogen bonding between PP and amino acid residues comes from molecular docking studies. Thus, we conclude that the n value of ∼1 determined by fluorescence quenching pertains to a high-affinity site for PP binding (probably involving van der Waals and electrostatic interactions) with the Apo-B100 receptor protein of LDL. There are additional low-affinity sites (where hydrogen bonding could act as the main driving force) at the Apo-B100 surface and/or the phospholipid outer shell that also can make a contribution that can be detected by the affinity column/HPLC method.…”
Section: Resultsmentioning
confidence: 70%
“…There are numerous reports of PP interacting by hydrogen bonding with lipids such as cholesterol and phospholipid bilayers and cell membranes using multiple techniques. A study in this Journal showed that tea catechins formed multiple hydrogen bonds with a phospholipid . Additional support of hydrogen bonding between PP and amino acid residues comes from molecular docking studies. Thus, we conclude that the n value of ∼1 determined by fluorescence quenching pertains to a high-affinity site for PP binding (probably involving van der Waals and electrostatic interactions) with the Apo-B100 receptor protein of LDL. There are additional low-affinity sites (where hydrogen bonding could act as the main driving force) at the Apo-B100 surface and/or the phospholipid outer shell that also can make a contribution that can be detected by the affinity column/HPLC method.…”
Section: Resultsmentioning
confidence: 70%
“…In addition, the binding forces between PL and QUE (among other flavonoids) presented the strongest binding combined to the highest inhibitory potency, mainly explained by its polar interactions due to its size and stringency of structure [62]. It was reported that F, L, isoleucine (I) and W residues play a major role in the dynamic of binding between proteins and flavonoid ligands according to: (i) flavonoids - amino acids (AA) binding energies, (ii) AA hydrophobicity, and (iii) the high number of AA involved in the binding sites of proteins [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, collective evidence demonstrates that nutritional conditions, dietary habits, bioactive compounds derived from food, and exercise prevent the age-dependent decline in memory and cognition (8)(9)(10). Many dietary foods, phytochemicals, herbal secondary metabolites, and polyphenols have pharmacological benefits for human diseases (11)(12)(13). Colourful berries, especially those rich in polyphenols, have revealed an improvement in the motor, memory, and cognitive functions that are deteriorated with aging in animals, including humans (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%